2009
DOI: 10.1681/asn.2009030283
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D Levels, Race, and the Progression of Kidney Disease

Abstract: Black individuals have lower 25-hydroxyvitamin D [25(OH)D] levels and experience a disproportionate burden of ESRD compared with white individuals. Animal studies suggest that vitamin D has renoprotective effects. We evaluated the contribution of low 25(OH)D levels on incidence of ESRD using data from the Third National Health and Nutrition Examination Survey-linked Medicare claims files (n ϭ 13,328). We included baseline (1988 through 1994) measurements of 25(OH)D and assessed the incidence of ESRD through Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
137
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 55 publications
7
137
2
3
Order By: Relevance
“…This is in line with previous studies (6,42), although others did report an association with renal function loss (43). The relatively small decrease in eGFR during follow-up (217.2 ml/min per 1.73 m 2 [IQR, 226.0 to 210.4]) may explain this negative result; studies with longer follow-up may be needed to further explore this association.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with previous studies (6,42), although others did report an association with renal function loss (43). The relatively small decrease in eGFR during follow-up (217.2 ml/min per 1.73 m 2 [IQR, 226.0 to 210.4]) may explain this negative result; studies with longer follow-up may be needed to further explore this association.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with the results of other studies 43,44 and may be related to increased skin pigmentation, which reduces the skin's ability to synthesize activated vitamin D. 45 The number of African American patients in this study is reflective of the hospital's urban Detroit population. According to data from the National Health and Nutrition Examination Survey, nonHispanic blacks and Mexican Americans are more likely to be at risk for vitamin D deficiency than are other races after adjustments are made for season and age.…”
Section: Financial Disclosures None Reportedsupporting
confidence: 92%
“…1,25(OH)D is less commonly measured than is 25(OH)D. Indeed, 1,25(OH)D status has not been assessed in most studies demonstrating a link between vitamin D deficiency and important clinical endpoints, including cardiovascular disease, 39 mortality, 40 certain types of cancer, 41 and, of note, ESRD 18 and GFR decline. 19 Because 25 (OH)D and 1,25(OH)D were systematically measured in this study, we could discriminate the relative association of these two measures with renal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] More recently, calcitriol and paricalcitol, two agonists of VDR signaling, have been shown to lessen albuminuria in patients with IgA nephropathy 16 and diabetic nephropathy, 17 respectively. In addition, two community-based studies and a small observational study in patients with CKD who have not had transplantation found an association between low 25(OH)D levels and the risk of ESRD 18 or eGFR decline. 19 Transplant recipients frequently have low 25(OH)D and 1,25(OH)D levels, especially early after transplantation.…”
mentioning
confidence: 99%